Comparison of blistering of W bulk and coatings under H₂, D₂ and He plasma irradiation - Nikitin, A.V.; Kuprin, A.S.; Tolstolutskaya, G.D.; Vasilenko, R.L.; Ovcharenko, V.D.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2018)
The surface topography of W bulk prepared by powder sintering (20 μm thickness) and W coatings deposited by cathodic arc evaporation and by argon ion sputtering was studied under the influence of low-energy hydrogen (deuterium) and helium plasma at room temperature. The surface modifications induced by the plasma irradiation were studied by scanning electron microscopy. It was observed formation of blisters and sputtering. After helium and deuterium plasma irradiation, numerous blisters were observed on the surface of W foils samples and coatings deposited by argon ion sputtering. The surface of W coatings deposited by cathodic arc evaporation was undergone only sputtering process under the same irradiation conditions. Вивчено зміну топографії поверхні масивного вольфраму, отриманого методом порошкового спікання (товщиною 20 мкм), і W-покриттів осадженими вакуумно-дуговим методом та іонним розпиленням під впливом низькоенергетичної водневої (дейтерієвої) і гелієвої плазми при кімнатній температурі. Поверхневі модифікації, індуковані плазмовим опроміненням, вивчалися за допомогою сканувальної електронної мікроскопії. Після опромінення гелієвою і дейтерієвою плазмою на поверхні зразків фольги W і покриттів, нанесених іонним розпиленням, спостерігалися численні блістери. Поверхня W-покриттів, осаджених вакуумно-дуговим способом, піддавалася тільки розпорошенню при тих же умовах опромінення. Изучены изменения топографии поверхности массивного вольфрама, полученного методом порошкового спекания (толщиной 20 мкм), и W-покрытий осажденными вакуумно-дуговым методом и ионным распылением под воздействием низкоэнергетической водородной (дейтериевой) и гелиевой плазмы при комнатной температуре. Поверхностные модификации, индуцированные плазменным облучением, изучались с помощью сканирующей электронной микроскопии. После облучения гелиевой и дейтериевой плазмой на поверхности образцов фольги W и покрытий, нанесенных ионным распылением, наблюдались многочисленные блистеры. Поверхность W-покрытий, осажденных вакуумно-дуговым способом, подвергалась только распылению при тех же условиях облучения.